Collaboration of Local Potentials in Supporting Sustainable Development (A Study in Kaserangan Village, Pontang Sub-District, Serang Regency) - Helmi Yazid; Ayu Regina Cahyawati; Fadya Aprilia; Ajeng Hartati; Vatya Almanda Putri; Siti Hartati Itaqi; Nusroh Milati; Dzakiyyah Huuriyatun Nisah; Mochamad Naufal Alawiyansyah; Ayaturohman Ayaturohman; Muhammad Annas Sudadi; Nesih Nesih; Farasya Nabila; Marsha Azzahra; Selfi Maharani; Olivia Monica; Farhah Kamylya Rahmah; Gina Mega Dwi Cahya; Tisna Wahyu Vernanda; Meilani Sri Ayuningsih; Tinka Vedyra Jotha; Aldo Devano; Zahroh Atiqah (MOVE: Journal of Community Service and Engagement, 2023)
Student Community Service (Kuliah Kerja Mahasiswa/KKM) is an activity that provides experiences in empowering communities which becomes a golden opportunity for students to express their ideas, innovations, and thoughts that sharpen critical thinking. Through the implementation of KKM, it is expected that students are able to develop social and personal competencies. The community service methods carried out by KKM Group 112 students are through KKM orientation, entrepreneurship counseling and mentoring for micro, small and medium enterprises (MSMEs), mutual cooperation activities, digital marketing education seminars, halal studies socialization, sexual violence socialization, and teaching at elementary schools and kindergartens. The target audience of this activity is the surrounding community of the KKM location, which consists of housewives, micro-business owners, and children of Kaserangan Village.